Analytical characterization using surface-enhanced Raman scattering (SERS) and microfluidic sampling. (13th February 2015) - Wang, Chao; Yu, Chenxu
Abstract: With the rapid development of analytical techniques, it has become much easier to detect chemical and biological analytes, even at very low detection limits. In recent years, techniques based on vibrational spectroscopy, such as surface enhanced Raman spectroscopy (SERS), have been developed for non-destructive detection of pathogenic microorganisms. SERS is a highly sensitive analytical tool that can be used to characterize chemical and biological analytes interacting with SERS-active substrates. However, it has always been a challenge to obtain consistent and reproducible SERS spectroscopic results at complicated experimental conditions. Microfluidics, a tool for highly precise manipulation of small volume liquid samples, can be used to overcome the major drawbacks of SERS-based techniques. High reproducibility of SERS measurement could be obtained in continuous flow generated inside microfluidic devices. This article provides a thorough review of the principles, concepts and methods of SERS-microfluidic platforms, and the applications of such platforms in trace analysis of chemical and biological analytes.